2020
DOI: 10.3389/fpsyg.2020.01915
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and Empathy: Mediating Factors and Gender Differences in a Spanish Sample

Abstract: Numerous research studies link mindfulness training to improved empathy. However, few studies focus on the mediating factors of empathy. This work has three objectives: (a) to analyze the possible mediation of mindfulness as a feature in this relation, (b) to analyze the mindfulness factors that mediate in the increase of empathy and (c) to analyze the moderating role of gender. The sample was composed of 246 Spanish-speaking university students (M = 24.08 years, SD = 8.43). The instruments used were the Five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 74 publications
3
6
0
Order By: Relevance
“…For example, the percentage of women in the area of education in the United Kingdom is 74%, in Ireland it is 68% and in Spain it is 81%, and with regard to the area of health and social services in the United Kingdom it is 79%, in Ireland it is 75% and in Spain it is 72%. Furthermore, in other recent studies on mindfulness, the gender distributions are similar to those in our research [ 3 , 44 , 45 ]. Finally, according to a recent review that analyzed the gender distribution of all published peer-reviewed trials on mindfulness [ 46 ], men accounted for less than 29% of nearly 10,000 participants.…”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…For example, the percentage of women in the area of education in the United Kingdom is 74%, in Ireland it is 68% and in Spain it is 81%, and with regard to the area of health and social services in the United Kingdom it is 79%, in Ireland it is 75% and in Spain it is 72%. Furthermore, in other recent studies on mindfulness, the gender distributions are similar to those in our research [ 3 , 44 , 45 ]. Finally, according to a recent review that analyzed the gender distribution of all published peer-reviewed trials on mindfulness [ 46 ], men accounted for less than 29% of nearly 10,000 participants.…”
Section: Methodssupporting
confidence: 91%
“…These factors are grouped into a general factor that contemplates the traits of mindfulness. The questionnaire has adequate psychometric guarantees of reliability and validity, and has good sensitivity to differences in mindfulness practice [ 3 , 44 , 51 ]. It has been validated in different languages and cultures, in countries such as Spain, France, the Netherlands, Germany, China, Norway and Chile [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results related to mindfulness show that there is no statistically significant difference between the scores of women and men. This result is in concurrence with the studies in which the moderation role of gender is tested and no statistically significant difference was found (de la fuente‐anuncibay et al, 2020; Kaviani & Hatami, 2016). As a result, H1 is partially confirmed.…”
supporting
confidence: 90%
“…For example, Martins et al (2019) found a statistically significant difference between girls and boys in terms of their ToM abilities. However, there have been conflicting results about the role of gender in mindfulness (Alispahic & Hasanbegovic‐Anic, 2017; De la Fuente‐Anuncibay et al, 2020). For example, in a mindfulness training intervention program, it was determined that female meditators had higher improvement than did the control group (Kang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%